Speciallärares och specialpedagogers relationskompetens i arbete med elevers kamratrelationer och med relationer till elevernas föräldrar - Jonas Aspelin; Anders Jönsson; Daniel Östlund (Dalarna university, 2024)
Research shows that educators' capability to build positive and supportive relationships is critical for educational success, particularly for at-risk students. The purpose of this article is to discuss how special educators - "speciallärare" (SL) and "specialpedagoger" (SP) - perceive relational competence working with their students' peer relationships and with the students' parents. The article presents an interview study of 21 experienced SL and SP. The findings indicate that SL and SP perceive relational competence as an extensive, complex, and advanced work involving short- and long-term dimensions, formal and informal social situations, and with instrumental and immanent purposes. Overall, SL and SP highlight relational competence through cooperation in which the other party is directly involved. Moreover, the thematic analysis shows that SL and SP perceive relational competence regarding peer relationships as manifested through (i) "social training", which is carried out spontaneously and by arrangement, and (ii) "relational mediation", which has a direct or an indirect form. In relation to students' parents, SL and SP perceive relational competence as manifested in direct interaction, which includes two aspects: (i) "guidance" and (ii) "confirmation". The article suggests that relational competence, as seen from the perspectives of SP and SL, can be understood in terms of method and encounters, dimensions that are important to notice in special education teacher training, as well as in further research.